Hydraulic Analysis of The Upper Segment of Cileungsi River, Bogor District Using Hecras 5.0.7 Program - Acep Hidayat; Febrianto Tri Prasetyo (NAROTAMA UNIVERSITY, Indonesia, 2021)
Regional Flow of the River Cileungsi has extensive DAS 266 , 15 km2 and a length of 39.11 km, crossing the district of Bogor and Bekasi. Downstream of the Cileungsi River is the Bekasi Hulu River which is the confluence of the Cileungsi River and Cikeas River . With the condition of land-use land DAS Cileungsi the first form forests changed into land estates and settlements led to discharge runoff were high and result in the occurrence of flooding in the summer rain . Flood prevention efforts are planned by making a dam . Analysis profiles flow conducted by using software HEC-RAS 5.0.7, Planning control flooding river Cileungsi using debit flood plan Q25th which amounted to 1271.45 m3 / sec and Q50th which amounted to 1376.99 m3 / sec. In the results of simulation of unsteady flow with HEC-RAS can be concluded that the control of flooding with the manufacture of a dam on the upstream river Cileungsi , already managed to overcome the flow of water excess in the upper reaches of the river